Revisiting the characteristics and ablation strategy of biatrial tachycardias: a case series and systematic review. Issue 3 (23rd December 2022) - Lai, Yiwei; Guo, Qi; Sang, Caihua; Gao, Mingyang; Huang, Lihong; Zuo, Song; Lu, Zhibing; Jiang, Chenxi; Li, Songnan; Guo, Xueyuan; Wang, Wei; Liu, Nian; et al.
Abstract: Aims: To describe the role of left atrial (LA) epicardial conduction and targets of ablation in biatrial tachycardias (BiATs). Methods and results: Consecutive patients with BiAT diagnosed by high-density mapping and appropriate entrainment were enrolled. A systematic review of case reports or series was then performed. Biatrial tachycardia was identified in 20 patients aged 63.5 ± 11.1 years. Among them, eight had LA epicardial conduction, including four via the ligament of Marshall, two via myocardial fibres between the great cardiac vein (GCV) and LA, one via septopulmonary bundle, and one via myocardial fibres between the posterior wall and coronary sinus. Ablation was targeted at the anatomical isthmus in 14, including 5 undergoing vein of Marshall ethanol infusion and 2 undergoing ablation in the GCV. Another six underwent ablation at interatrial connections, including one with septopulmonary bundle at the fossa ovalis and five at the atrial insertions of Bachmann's bundle. After a mean follow-up of 8.7 ± 3.8 months, five patients had recurrence of atrial fibrillation/flutter. Systematic review enrolled 87 patients in previous and the present reports, showing a higher risk of impairment in atrial physiology in those targeting interatrial connections (30.4 vs. 5.0%, P < 0.001) but no significant difference in short- and long-term effectiveness. Conclusion: Left atrial epicardial conduction is common in BiATs and affects the ablation strategy. Atrial physiology is a major concern in selecting the target of intervention. Graphical Abstract: Graphical Abstract